Training load and recovery during a pre-Olympic season in professional rhythmic gymnasts - Barreiros Debien, P.; Miloski, B.; Zacaron Werneck, F.; Ferreira Timoteo, T.; Ferezin, C.; Bara Filho, M. G.; Gabbett, T. (Journal of Athletic Training, 2020)
Context: Rhythmic gymnastics requires a high level of complexity and perfection of technical gestures, associated with well-developed physical and artistic capacities. The training-load and recovery profiles of rhythmic gymnasts across a season are unknown. Objective: To analyze the training load and recovery of professional rhythmic gymnasts during 1 season. Design: Cohort study. Setting: Brazilian National Training Center of Rhythmic Gymnastics and competition facilities. Patients or Other Participants: Eight gymnasts from the Brazilian national senior rhythmic gymnastics group. Main Outcome Measure(s): Session rating of perceived exertion (session-RPE) and total quality recovery (TQR) scores were collected daily for 43 weeks. We obtained the session-RPE after each session and TQR score before the first session of the day. Performances during 5 competitions were also recorded. The season was divided into 8 periods. Total weekly internal training load (wITL), training intensity, frequency, duration, recovery, and acute : chronic workload ratio were calculated for analysis. Results: The season mean wITL was 10 381 ± 4894 arbitrary units, mean session-RPE score was 5.0 ± 1.6, and mean TQR score was 12.8 ± 1.3. The gymnasts trained an average of 8.7 ± 2.9 sessions per week, with a mean duration of 219 ± 36 minutes. Each competitive period showed increased wITL compared with the previous period. Training-load variables (wITL and session-RPE) and recovery were inversely correlated. Gymnasts were poorly recovered (TQR < 13) during 50.9% of the season (n = 167 times), especially during competitive weeks. Spikes in load (acute : chronic workload ratio = 1.5) occurred across 18.1% of the season (n = 55 times). Conclusions: The training-load variables and recovery changed throughout a professional rhythmic gymnastics group season, mainly during competitive periods. The correct distribution of training load is critical to ensure that gymnasts are entering competitions in a recovered state.